Performing each repetition at maximum velocity produces greater gain in strength compared to performing each repetiton at 50% of the maximum voluntary velocity - Pareja-Blanco, F.; Rodriguez-Rosell, D.; Otero-Esquina, C.; Mora-Custodio, R.; Gonzalez-Badillo, J. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
When designing resistance programs to optimize athletic performance a key variable used is training velocity. To be specific, the intention to move a load explosively has been regarded as well suited for developing strength at high contraction velocities (1). This study compares the effects of performing each repetition at maximum voluntary velocity, by measuring the exact velocity of each repetition. Methods: Twenty-one young and healthy men to take part in this study [mean (SD): age 22.3(3.2) yr, body weight 72.6(9.2) kg, height 1.77(0.07) m], were randomly assigned to one of two groups: maximum voluntary velocity (V100; n=10) or 50% of maximum velocity (V50; n=11) with each load. Subjects trained during 6 wk for a total of 18 sessions following a periodized resistance training program using the full squat. The two groups trained at the same relative intensity in each session (increasing from 60% to 80%RM) but differed in the velocity reached in each repetition (100% vs. 50% of maximum possible velocity). Velocity was monitored in each session (T-Force System, Ergotech, Spain). A covariance test was used to compare the changes between the groups. A t-test for paired samples was used to compare pre-test and post-test measurements in each group. Results: Both groups obtained significant increases in 1RM strength (18.6% vs. 10.3%), mean velocity with absolute loads common to both test (MV) (15.9% vs. 7.5%) and CMJ (8.7% vs. 2.5%) in V100 (p<0.01) and V50 (p<0.05), respectively. Furthermore, on comparison, V100 had significantly higher gains (p<0.01) for CMJ than V50. Discussion: These results indicate that short-term velocity-based resistance training produces greater neuromuscular performance improvement when performing each repetition at maximum velocity. Several studies show that training to maximal voluntary velocity produces greater improvements in rate of force development and power, and similar gains in strength (2-3). In addition, the present study shows greater improvements in physical performance measured by CMJ.